2012
DOI: 10.1111/1365-2435.12014
|View full text |Cite
|
Sign up to set email alerts
|

The size‐number trade‐off in clonal broods of a parasitic wasp: responses to the amount and timing of resource availability

Abstract: Summary1. Life-history traits that shift in response to environmental conditions are well studied; however, allocation patterns of traits in the context of a trade-off shifting with the environment are hardly examined. 2. Using a polyembryonic parasitoid wasp system, we revealed features of the plasticity in allocation by observing the trade-off outcome between individual body mass and the number of offspring in a wasp brood in response to different host conditions. 3. We manipulated food availability to the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…Recent studies have demonstrated the importance of the timing of nutritional deprivation on success in adulthood [19,20], which may have independent or interactive effects on the expression of adult phenotypes. Distinct stages may often exist in the developmental processes of organisms when nutritional variation has disproportionately large effects on phenotypic expression [21], including effects on disease susceptibility in later life [22] and adaptive polyphenisms, such as the winged phase switch in pea aphids, Acyrthosiphon pisum [23] or horn elongation in dung beetles, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated the importance of the timing of nutritional deprivation on success in adulthood [19,20], which may have independent or interactive effects on the expression of adult phenotypes. Distinct stages may often exist in the developmental processes of organisms when nutritional variation has disproportionately large effects on phenotypic expression [21], including effects on disease susceptibility in later life [22] and adaptive polyphenisms, such as the winged phase switch in pea aphids, Acyrthosiphon pisum [23] or horn elongation in dung beetles, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…1. An example of each tradeoff component, based on studies of a parasitoid wasp exploiting its host (Saeki et al 2009, Crowley and Saeki 2009, Saeki and Crowley 2012, 2013), is shown to the right of each component. The constraint is the amount or supply rate of the limiting resource (e.g.…”
Section: Definitions and Logicmentioning
confidence: 99%
“…As a polyembryonic parasitoid, C. bakeri produces large clonal broods, permitting precise, sex‐specific assessment of the tradeoff. In Saeki et al (2009) and Saeki and Crowley (2013), most components and relationships of Fig. 1 were measured for both sexes and in different environments (Saeki and Crowley 2012, 2013).…”
Section: Three Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms underlying these determinations of brood size and body size have been examined during the preemergence interval Saeki & Crowley, 2012, 2013). Our previous work showed flexible shifts in both brood size and body mass depending on host quality, whereas female-biased sexual size dimorphism was robust.…”
Section: Fitness Components and Size-number Trade-off 245mentioning
confidence: 99%